Peran BAPPEDA Provinsi Sumatera Utara dalam Penerapan Pembangunan Daerah Berdasarkan Permendagri No. 70 Tahun 2019 tentang Sistem Informasi Pemerintah Daerah - Fandy Enko Irwanto S.; Dayat Limbong; Isnaini Isnaini (Mahesa Research Center, 2021)
This article aims to identify and analyze the rule of law, the role and constraints faced by the Bappeda of North Sumatra Province in regional development. 70 of 2019 concerning Local Government Information Systems. This type of research is normative by using qualitative analysis. The results of the study found that the legal regulations for regional development planning are regulated in Law Number 25 of 2004 concerning the National Development Planning System and Minister of Home Affairs Regulation number 54 of 2010. The North Sumatra Bappeda has a role in formulating technical policies, regional development planning, research and development starting from the strategy, policy direction, macroeconomic framework, development of regulatory framework, institutions and funding in accordance with the policies determined by the regent based on the prevailing laws and regulations.